Serial Default and the “Paradox” of Rich-to-Poor Capital Flows - Reinhart, Carmen M; Rogoff, Kenneth S (American Economic Review, 2004)
Lucas (1990) argued that it was a paradox that more capital does not flow from rich countries to poor countries. He rejected the standard explanation of expropriation risk and argued that paucity of capital flows to poor countries must instead be rooted in externalities in human capital formation favoring further investment in already capital rich countries. In this paper, we review the various explanations offered for this “paradox.” There is no doubt that there are many reasons why capital does not flow from rich to poor nations – yet the evidence we present suggests some explanations are more relevant than others. In particular, as long as the odds of non repayment are as high as 65 percent for some low income countries, credit risk seems like a far more compelling reason for the paucity of rich-poor capital flows. The true paradox may not be that too little capital flows from the wealthy to the poor nations, but that too much capital (especially debt) is channeled to “debt intolerant” serial defaulters.